Validity and Reliability of Turkish Version of Perception of Health Scale - KADIOĞLU, HASİBE (ORTADOGU AD PRES & PUBL CO, 2012)
Objective: The aim of this study was to run the validity and reliability studies of Turkish adaptation of Perception of Health Scale developed by Diamond et al. (2007). Material and Methods: This study was done methodologically. Perception of Health Scale is a quintet quintette likert type scale composed of 15 items and four sub-factors. The scale was translated from English to Turkish using the back-translation technique. It was applied to students of nursing schools of two universities in Istanbul (n=287) and their family members (n=307). Validity of the scale was evaluated with factor analysis and content-scope validity and reliability was evaluated with item-total score correlation, internal consistency and continuity methods. Kendal W analysis was used for content validity, Cronbach's alpha coefficient was used for internal consistency, Pearson correlation analysis was used for item analysis and test-retest analysis. Results: Content validity was evaluated with opinions of 6 experts and between expert opinions about items of the scale was not found statistically significant difference (p=0.563). Correlation values of scale items was found above 25 for all items as the result of item total score analysis. Cronbach's alpha coefficient was found as 77 in nursing students and 70 in the families of the students. As the result of factor analysis, items of the scale was found to gather under four factors expalining 53.21% of total variance. Pearson's correlation value was found as 0.78 in retest (p=0.000). Conclusion: Turkish version of Perception of Health Scale was decided to be a valid and reliable scale.
Keywords: Perception; reproducibility of results